Advances in retinal imaging biomarkers for the diagnosis of cerebrovascular disease - Zhang, Yier; Zhao, Ting; Ye, Ling; Yan, Sicheng; Shentu, Wuyue; Lai, Qilun; Qiao, Song (Frontiers in Neurology, 2024)
The increasing incidence and mortality rates of cerebrovascular disease impose a heavy burden on both patients and society. Retinal imaging techniques, such as fundus photography, optical coherence tomography, and optical coherence tomography angiography, can be used for rapid, non-invasive evaluation of cerebral microcirculation and brain function since the retina and the central nervous system share similar embryonic origin characteristics and physiological features. This article aimed to review retinal imaging biomarkers related to cerebrovascular diseases and their applications in cerebrovascular diseases (stroke, cerebral small vessel disease [CSVD], and vascular cognitive impairment [VCI]), thus providing reference for early diagnosis and prevention of cerebrovascular diseases.